STUDENT'S SELF-ESTEEM AND ITS INFLUENCE ON SPEAKING ABILITY AT SECONDARY SCHOOLS IN LAMPUNG - Rahma, Eva Agustina; Wahyudin, Achmad Yudi (Indonesian Journal of Educational Development (IJED), 2024)
This study focuses on the relationship and influence between students' self-esteem and students' English ability. Speaking is an important language skill, especially in a global setting where English is required for success in many areas. The study's goal is to evaluate if self-esteem has a substantial influence on students' speaking ability, as well as to uncover variables that contribute to poor self-esteem. Data were collected from 10th graders at a public school in South Lampung using questionnaires, speaking exams, and interviews. Using Pearson's correlation in SPSS.26, a sample of 36 students yielded a correlation value of 0.446, demonstrating a modest positive association between self-esteem and speaking ability. Peer comparison, dependence on external validation, emotional responses to failure, family dynamics, social support, and instructor evaluation are all factors that influence one's self-esteem. Addressing these issues is critical for increasing students' resilience and cultivating a more positive self-image, which can lead to improved speaking ability.